Skala Keekonomian Terkecil Pabrik Bioplastik Starch-Cellulose Blend Berbahan Baku Tandan Kosong Kelapa Sawit - Edi Djatmika; Hermawan Hermawan; Sawarni Hasibuan; Bambang Wahyudiono (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Empty oil palm bunches processed by palm oil mills in Indonesia are still abundant, reaching 56.35 million tons per year. Empty oil palm bunches contain around 40% cellulose, so they can still be used for various derivative products, one of which is composite products. The use of empty oil palm bunches as raw materials for Bioplastic production is a series of ongoing research, one of which is starch-cellulose blend, but until now it has not been successfully commercialized. The design of the starch cellulose blend bioplastic industry using palm oil as raw material produces two factories, namely a cellulose factory and a composite bioplastic factory. Both factories are designed in separate buildings. The separation of cellulose from TKKS uses a chemical method with soda, after mechanical treatment of size reduction. The industry is designed in 3 scales of production capacity, namely a large scale of 190,000 tons / year, medium 115.00 tons / year, and small 40,000 tons.year. The financial analysis of the three scales of production capacity as a whole is declared feasible. Profit margin is calculated at a minimum of 17.6%. The average payback period is between 3-5 years with an IRR of 24-49%. Analysis of the economic value produces an EScale index of 0.64 which indicates that the economic scale has been achieved. The economic scale of the starch cellulose blend bioplastic industry from TKKS is at a production capacity of 40,000 tons per year with a minimum supply of TKKS raw materials of 20,203 tons/year. At the smallest economic scale, the BEP is actually only 6627.4 tons/year, where this condition can be achieved because the industry has relatively small fixed costs.